A Study on QT Dispersion before and After Thrombolysis in Acute Myocardial Infarction and Its Prognostic Implications: A before and After Comparison Study. - Reddy. V, Amulya; Prabhakar K, Prabhakar K; Anitha A, Anitha A (Journal of Neonatal Surgery, 2025)
Background and Objectives: Acute myocardial infarction (AMI), particularly ST-segment elevation myocardial infarction (STEMI), is associated with increased morbidity and mortality. QT dispersion (QTd), a measure of ventricular repolarization heterogeneity, is known to predict arrhythmic risk. This study evaluates changes in QT, corrected QT (QTc), QTd, and corrected QT dispersion (QTcd) before and after thrombolysis in STEMI and their prognostic relevance. To assess changes in QT interval parameters before and after thrombolytic therapy in STEMI patients and explore their implications for arrhythmia prediction and short-term clinical outcomes. Methods: This prospective, observational before-and-after study was conducted over three months in the ICU of R.L. Jalappa Hospital, Kolar. A total of 25 STEMI patients undergoing thrombolysis were enrolled. Standard 12-lead ECGs were obtained before and 90 minutes after thrombolysis. QT, QTc, QTd, and QTcd were manually measured. Statistical analysis was performed using paired t-tests, with p < 0.05 considered significant. Results: The mean age was 58.4 ± 10.2 years, with a male predominance (72%). Post-thrombolysis, QT interval decreased significantly from 0.37 ± 0.06 s to 0.34 ± 0.05 s (p=0.001); QTd reduced from 68.4 ± 12.3 ms to 52.6 ± 10.8 ms (p<0.001); QTcd declined from 76.2 ± 13.4 ms to 59.8 ± 11.7 ms (p<0.001). Greater reductions in QT dispersion were seen in anterior wall MI and those receiving thrombolysis within 3 hours. Eight patients (32%) experienced reperfusion arrhythmias. Higher post-thrombolysis QT dispersion was associated with complications such as heart failure (p=0.04) and mortality (p=0.01). Conclusion: Thrombolysis significantly reduces QT and QT dispersion parameters, indicating improved electrical stability post-reperfusion. Higher residual QT dispersion post-thrombolysis may predict adverse short-term outcomes, suggesting its potential role as a non-invasive prognostic tool in STEMI management.